Evaluating implementation of an Heat-health action plan during 2018 heatwave in Amadora, Portugal. (13th November 2019) - Leite, A; Cabral, M; Rodrigues, E; Vaz, D; Calé, E; Silva, A C
Abstract: Issue: Heatwave-health effects are preventable. Heat-health action plans (HHAPs) include preventive measures aimed at protecting population. In Portugal, HHAPs exist since 2004 and have been operationalized at local level. Heatwaves occur infrequently, thus experience with HHAPs is relevant to countries implementing their own HHAPs. Description: In the summer of 2018, Amadora (Lisbon, Portugal) issued a warning from the 2nd-6th August (highest level:4th-6th). Before/during the warning we implemented: 1.climatized shelter opened available upon request;2.text messages with recommendations and information on the walk-in clinic services available;3.information to nursing homes regarding available services (walk-in services/shelter);4.contact with individuals receiving home support and identified as vulnerable. Nationwide media publicity of individual protection measures was also ongoing. We aimed at evaluating these HHAP measures. We compared demand of walk-in clinic (primary care) and emergency department with existing capacity, updated during the heatwave. Mortality was analysed using an observed-expected ratio (O/E) of week 32 (following the heatwave) and 95% confidence interval (95%CI) under a Poisson distribution. Expected deaths were the average deaths in week 32 of the previous 4 years (2014-17). Results: In the primary care walk-in clinic the demand was ½ of capacity; hospital emergency services demand did not increase. We had no requests for the shelter unit. Regarding mortality, O/E was 1.57 (95%CI:1.12-2.14). These results are preliminary; we are producing more detailed analyses of mortality data. Lessons: We have no counterfactual to assess the effect of our HHAP but our results indicate the possibility to reduce heatwaves-mortality further and thus the need for additional measures. We did not observed the expected surge in service demand; the adequacy of supply-based measures is currently under debate. More detailed mortality analysis will provide further insights. Key messages: We implemented several measures during a heatwave in Amadora, Portugal with no increased demand in available health services in the area. We detected an increased mortality following the heatwave, suggesting the need to implement further measures.